Manajemen Nyeri dengan Guided Imagery pada Pasien Pasca Operasi Total Joint Arthroplasty - Ahmidati, Afiif; Irawaty, Dewi; Yona, Sri; Arista, Liya (Journal of Telenursing (JOTING), 2024)
This study aims to identify the effectiveness of guided imagery in patients after total joint arthroplasty surgery. The method used is a systematic review using literature searches from 9 databases: PubMed, Scopus, Sage, ScienceDirect, Taylor & Francis, Wiley, SpringerLink, Cochrane, and ProQuest. Fifteen thousand seven hundred forty-eight articles were obtained from the initial search using keywords related to "Total Joint Arthroplasty,"; "Guided Imagery," and "Pain," but only five articles met the inclusion criteria for this study, namely adult and elderly patients after total joint arthroplasty, period 2021 - 2024, in English, full-text and open access. The five research articles showed that guided imagery significantly reduced pain after total joint arthroplasty. In conclusion, guided imagery effectively reduces pain in patients after total joint arthroplasty surgery. Guided imagery is used because it is easy to do, teach, and affordable. Keywords: Guided Imagery, Pain, Total Joint Arthroplasty